Adsorption of Eosine Y Dye using Modified Eggshell Adsorbent for Sustainable Water Treatment - Sangoremi, Abidemi Anthony (FUDMA Journal of Sciences, 2026)
Synthesis and application of modified eggshell-based adsorbent (MESBA) for the removal of Eosine Y dye from simulated wastewater as alternative technologies for wastewater treatment were investigated. The MESBA was characterised for physicochemical properties with the use of Fourier Transform Infrared (FTIR), Scanning Electron Microscope (SEM), and Energy Dispersive Spectrometer (EDS) as characterization tools respectively. The effect of adsorbent dosage on percentage dye removal was assessed. The isotherm data were fitted to Langmuir and Freundlich isotherm models by employing the linear and non-linear forms of the equations. MESBA has pH (7.80), moisture content (12.90%), ash content (5.80%), volatile matter (9.90%) fixed carbon (71.40%), bulk density (1.33 g/cm3), particle size (300 µm) and surface area (800 m2/g). The adsorbent possessed high carbon content with large surface areas in addition to the availability of functional groups within the adsorbent’s surface that are good adsorption sites for the removal of ES-Y dyes from wastewater. The adsorbent percentage dye removal was dosage-dependent at optimum dosage of 0.8 g. MESBA has maximum percentage dye removal of 82% at optimum dosage. The isotherm model that fairly described the removal of ES-Y dyes from wastewater was Freundlich isotherm model with coefficient of determination values for both linear (R2 =0.6746) and non-linear (R2 = 0.8615) form of the equations. Largely, the prepared adsorbent is efficient, eco-friendly and economically feasible in remediating dye-polluted wastewater, ensuring water reuse and regulatory compliance.
Keywords: Regulatory compliance, Water reuse, Freundlich isotherm, Dosage, Non-linear